Contraceptive Selection among Couples of Childbearing Age in the Perspective of Healthcare Workers: Original Article - Prihatiningsih, Riska Dwi; Indrawan, I Wayan Agung; Setijowati, Nanik (Babali Publisher, 2024)
Background: Women are susceptible to unwanted pregnancies. This makes them susceptible to risk factors such as maternal mortality, abortion, and stress. This study aims to explore health workers' perspectives on contraceptive selection among couples of childbearing in East Lombok Regency. Methods: Qualitative research design was employed with an interpretive phenomenological approach. This study was conducted in 4 Public health centers (PHCs) in East Lombok Regency, namely the Montong Betok PHC, Wanasaba PHC, Selong PHC, and Denggen PHC between May and June 2024. There were 12 participants consisting of 2 doctors, 8 midwives, and 2 nurses, recruited by purposive sampling. Data was collected using a recording device through in-depth interviews and field notes. Data were analyzed using a process based on four stages: transcribing, organizing, recognizing, and coding. Results: Eight themes emerged through data analysis, including 1) the role of health workers in contraceptive selection, 2) provider factors, 3) contraceptive availability, 4) access to contraceptive services, 5) cost of contraceptive use, 6) provision of contraceptive information by health workers, 7) social influences, and 8) fears and myths about contraception. Conclusion: Many factors influence contraceptive choice, but social influence is the most critical factor that determines whether couples of childbearing age choose and use contraception